O Porto e o comércio do vinho : dos alvores de setecentos à instituição da Real Companhia (1756) - Cardoso, António Barros (2001)
This paper is a concise study of the major guidelines of the research conducted by the author for his doctoral dissertation on the different relationships between the town of Oporto and the Douro region, based on a central element for the economic development of both areas: the wine production.